The Influence of Learning Styles on Understanding the Concept of Nanotechnology Material for Grade X High School Students in Indonesia - Bisri Mustopa; Mbuthia Ngunjiri; Abiodun Akinola Oladiti; Estácio Dinazarte Omar Rajá (Education Specialist, 2025)
Nanotechnology is one of the rapidly developing fields of science, promising innovation and application of technology on a nanoscale. Along with technological advances, the integration of Nanotechnology in various aspects of life is becoming increasingly important, including in education. For example, the use of nanotechnology-based ink can improve the quality of printing in textbooks and learning materials, making text easier to read and images clearer.This study aims to investigate the influence of learning styles on the understanding of Nanotechnology concepts among high school students. The focus of this study is on the comparison between learning methods adapted to learning styles and conventional methods. The main questions of this study are whether learning methods adapted to students'' learning styles have a significant influence on the understanding of Nanotechnology concepts compared to conventional methods, and how the understanding of Nanotechnology concepts compares between the two groups.The table above shows the distribution of students'' learning styles in the experimental class based on three categories: visual, auditory, and kinesthetic. Of the total 16 students, 37.50% or 6 students have a visual learning style, which means they find it easier to understand information through sight such as pictures, diagrams, or reading. 31.25% or 5 students have an auditory learning styleFrom the results and discussions above, it can be concluded that the Ho hypothesis is rejected and the Ha hypothesis is accepted.